Critical Illness Neuromuscular Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Four children with critical illness neuromuscular disease following prolonged dependency on a ventilator are reported from the Departments of Neurology and Pediatrics, West Virginia University Health Sciences Center, Morgantown, and the Department of Medicine (Neurology), Memorial University of Newfoundland, St John's, Canada.